CONTINUUM AND TIME IN MYTH - Ryazanova, S.V. (Perm Federal Research Centre Journal, 2015)
This article describes the basic regularities of the myth’s existence as a form of worldview, and the basis for selecting the way of social existence. Myth is analyzed as an essential phenomenon of culture. The main aspects of connection between ritual and myth are considered.